1.1k views
2 votes
Which of the following is a solution to the inequality y < –2x + 3?

User PGOnTheGo
by
5.5k points

1 Answer

6 votes

Answer:

y < -2x +3

A. (1, 1) → x = 1, y = 1

substitute:

1 < -2(1) + 3

1 < 1 FALSE

B. (3, 0) → x = 3, y = 0

substitute

0 < -2(3) +3

0 < -3 FALSE

C. (-3, 10) → x = -3, y = 10

substitute

10 < -2(-3) +3

10 < 9 FALSE

D. (0, 0) → x = 0, y = 0

substitute

0 < -2(0) + 3

0 < 3 CORRECT

Answer: D. (0, 0)

Explanation:

User Viral Patel
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.